Effects of L-Isoleucine Supplementation in the Diet on the Growth Performance of Kampong Chicken at the Starter Phase (1-6 Weeks) - Lisnahan, Charles Venirius; Pardosi, Lukas; Nahak, Oktovianus Rafael (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
This study aimed to determine the effect of L-isoleucine supplementation in the diet on the growth performance of Kampong chickens at the starter phase (1-6 weeks). This study was conducted at Kefamenanu, East Nusa Tenggara Province, Indonesia, from May to June 2023. A total of two hundred and fifty-week-old Kampong chickens with an average initial weight of 59.03±0.52 g were used in the study. The chickens were divided into five treatments with five replications based on a completely randomized design. The diet treatments were: T0 (control feed); T1 (T0 + 0.20% L-isoleucine, NRC, 1994 for broilers); T2 (T0 + 0.30% L-isoleucine); T3 (T0 + 0.40% L-isoleucine); and T4 (T0 + 0.50% L-isoleucine). The parameters observed were body weight, weight gain, feed intake, feed conversion ratio, carcass weight, and carcass percentage. The data obtained were analyzed using variance analysis and the Duncan test. The study result showed that the groups T3 and T2 had the highest body weight (330.76±1.29; 334.48±1.47 g/bird, respectively). The highest weight gain was in group T2 (275.54±1.39 g/bird/5 weeks). Group T3 had the highest feed intake (613.15±5.79 g/bird/5 weeks) and the lowest feed conversion ratio (2.22±0.02). The highest carcass weight was in groups T2 and T3 (189.95±1.17 and 189.32±0.65 g/bird, respectively), while the highest carcass percentage was in group T2 (57.43±0.47 %/bird). The statistical analysis indicated that body weight, weight gain, feed conversion ratio, and carcass weight were affected by the level of L-isoleucine (p<0.05). In contrast, feed intake and carcass percentage were not significant. It was concluded that supplementation with 0.40% L-isoleucine to the diet of Kampong chicken resulted in optimal growth performance at the starter phase (1-6 weeks).